Treatment and outcomes of patients in the Brain Metastases in Breast Cancer Network Registry - Witzel, I.; Laakmann, E.; Weide, R.; Neunhoeffer, T.; Park-Simon, T. -J.; Schmidt, Marcus; Fasching, Peter; Hesse, T.; Polasik, A.; Mohrmann, S.; Wuerschmidt, F.; Schem, C.; et al. (European Journal of Cancer, 2018)
Brain metastases (BMs) have a major impact on life expectancy and quality of life for many breast cancer patients. Knowledge about treatment patterns and outcomes is limited.We analysed clinical data of 1712 patients diagnosed with BMs from breast cancer between January 2000 and December 2016 at 80 institutions.Median age at diagnosis of BMs was 56 years (22-90 years). About 47.8% (n = 732) of patients had HER2-positive, 21.4% (n = 328) had triple-negative and 30.8% (n = 471) had hormone receptor (HR)-positive, HER2-negative (luminal-like) primary tumours. The proportion of patients with HER2-positive BMs decreased comparing the years 2000-2009 with 2010-2015 (51%-44%), whereas the percentage of patients with luminal-like tumours increased (28%-34%; p = 0.0331). Patients with BMs in the posterior fossa were more often HER2 positive (n = 169/314, 53.8%) than those diagnosed with triple-negative (n = 65/314, 20.7%) or luminal-like primary breast cancer (n = 80/314, 25.5%), (p < 0.0001). Median overall survival (OS) time after development of BMs for the overall cohort was 7.4 months (95% confidence interval [CI]: 6.7-8.0 months). One-year survival rate was 37.7% (95% CI: 35.2-40.1). Patients with HER2-positive tumours had the longest median OS of 11.6 months (95% CI: 10.0-13.4) compared with 5.9 months (95% CI: 5.0-7.2) for patients with luminal-like and 4.6 months (95% CI: 3.9-5.4) for patients with triple-negative tumours. Patients with HER2-positive tumours who received anti-HER2 treatment had longer median OS than those without (17.1 months versus 7.2 months, p < 0.0001).Prognosis of patients after developing BMs varies significantly according to the subtype. The outcome in this cohort is similarly poor in triple-negative and HR-positive/HER2-negative patients. Our results underline the high medical need for improvement of treatment and prevention strategies for BMs in breast cancer patients.
EVALuna2:56176